ETIKA HAMKA Konteks Pembangunan Moral Bangsa Indonesia - Muhammad Taufik (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2021)
The theme in this paper is about the ethical principles of HAMKA in the context of moral development in Indonesia. The theme of ethics is commonly discussed in various scientific works, but what makes it interesting is that he is one of the greatest thinkers in Indonesia who is also known as a scholar, writer, expert on Sufism, and as a philosopher. This is what underlies the author to examine and seek answers to the problem formulas, namely how is the concept of HAMKA ethics and how are the principles of HAMKA ethics in the context of moral development of the Indonesian? The method I use is a qualitative research method in the form of library research, namely by using the content analysis method. The content of each material can be in the form of sources from books, journals, or articles that are relevant to the topics that have been investigated, analyzed, and synthesized to form a complete concept in answering research questions. The result of this research is that HAMKA ethics has the characteristics of rational-religious ethics. HAMKA made the basis of its ethics from Greek ethical concepts to Muslim philosophers such as Ibn Miskawaih and al-Ghazali. HAMKA synthesizes ethical thoughts from philosophers with moral values taught by Islam through the Qur'an and Hadith.